(3GdHSW hGdJYQja aj Yde eG Ld ef GdJUQjas - (3CHhRjO YHO GdQMef Hf Ydj GdechOj GdaGSj,J (B807 (3g` s
(3ChdgG (B:s
(3hHYO aGfbUO HPG GdJUfja fXe bhGYO ef GdJUQja LeYJg QLR TWhQ dchfg ef CYRH GdHMhQ s
(3BNQgG (B:s
(3fLR HMeO Gddg s
(3hgj efXheI ai GdUQas
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B318s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdUQas